La buena administración pública como derecho de los ciudadanos y la eficacia del Código Orgánico Administrativo. - Valle Melena, Eric Sebastian (2023)
A renewed vision of Administrative Law has achieved that public administrations aim to be entities of quality and with a service to the general interest, so the right to good public administration has been established in different legislations. This way, it is achieved that public sector entities comply with the agenda of modern Administrative Law, although in our country, that reality does not exist. This right that emerged in Europe with the European Charter of Fundamental Rights in the year 2000 was born with the intention that all public entities be effective and efficient. This concept has been developed more and more over the years. By 2013, the Ibero-American Charter of Rights and Duties of the Citizen concerning Public Administration was issued, with which Ecuador and some Ibero-American countries visualize this new right. It was not until 2018 that we saw for the first time the fundamental right to good administration as such, typified in Article 31 of the Administrative Organic Code. However, this right does not have a specific scope recognized. This research will study what good administration is and can become from a doctrinal, legal, and constitutional perspective.